Variation of industrial localization transactions and operational efficiency of industrial activities in Erbil Governorate - ABDULKADHIM, ZINAH; Abdul-Rada, Wasan (Al-Adab Journal, 2024)
Industry represents the basic pillar of the economic structure in the region and a strong engine for the process of economic and social development. Industry is also an economic activity that has flexibility and great freedom of movement in the geographical space as well as the industrial sector the ability to create mutual relations between industrial localization transactions. This research came to studies of industrial localization transactions for manufacturing industries in Erbil Governorate for the year 2021 and their spatial variation according to administrative units of concentration and localization. The most prominent conclusions reached by the research were:The value of labor coefficients (labor force) in Erbil governorate for the year 2021 is focused on industrial establishments for the manufacture of food products by (24.4%) for labor plants, and the semi-metallic metals industry by (23.3%) at the expense of other manufacturing industries.The research revealed the concentration of the value of wages and salaries of labor in industrial establishments for the manufacture of food products by (35.7%) at the level of the province of Erbil compared to other manufacturing industries.